PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR DESA PADANG SAMBIAN KELOD – DENPASAR - Ni Nyoman Ayu Pebri Trinita; Putu Bagus Suthanaya (Universitas Triatma Mulya, 2021)
The purpose of this study was to determine the effect of leadership style and motivation on employee performance. Research data were collected by distributing questionnaires. The number of samples is 50 respondents. The research method uses quantitative and qualitative analysis. The analysis tool uses multiple linear regression analysis and t test. The results of the multiple linear regression analysis: Y = 14.075 + 0.268X1+ 0.262X2 indicate that the leadership style (X1) and motivation (X2) are assumed to be equal to 0 (zero), then employee performance (Y) will increase. Significance test using t test obtained tcount (X1) and tcount (X2) is greater than t table of (2,158) and (2,079) greater than (2,012), is in the area of rejection of Ho, this means partially leadership style and motivation have an effect positive and significant impact on employee performance at the Padangsambian Kelod Village Office Denpasar.